Perobahan dimensi hasil cetakan alginat berbentuk balok - Sumadhi Sastrodihardjo (DiscoverSys Inc., 2008)
There are several causal possibilities developing dimensional changes on impressionsuch as type of impression materials used, impression taking technique, bulk ofimpression material or size of impression tray. In this study investigation was done onthe size of impression material used to elucidate the possibilities role of impressionmaterial in gaining dimensional changes of impression. Rectangle shape alginateimpressions were made in 29.57 mm length, 19.45 mm width and 9.67 mm thicknessmold of metal master die covered by glass plate and dimensional changes aremeasured on alginate impression itself. Then data were analyzed with T-test (pairedsamples test)to compare dimension changing between alginat height anddimension changing on length and width. Measured results show the dimensionalchanges occur 3.16% ± 0.63% on length side, 3.35% ± 0.42% on width side and10.87% ± 1.01% on thickness side, respectively. There are significantly differences ofdimensional changes on thick ness side covered by glass plate compared withdimensional changes on length and width sides surrounding by metal of master die.